2007
DOI: 10.1111/j.1440-6055.2007.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation of termiticides under field conditions

Abstract: Soil testing is used by regulatory agencies to determine the adequacy of termiticide application by pest controllers. Because tests may be carried out years after treatment, an accurate knowledge of termiticide degradation rates is crucial if determinations are to be valid. Degradation of exposed residues of bifenthrin, chlorfenapyr, chlorpyrifos, fipronil and imidacloprid was investigated in a field trial conducted near Narrandera (inland New South Wales) and in Sydney. Samples of soil 75 mm deep were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Cox et al (1997) conducted sorptiondesorption of imidacloprid and its three metabolites and reported that metabolites such as the imidacloprid-guanidine, possibly produced in our experiment, are more strongly sorbed with the soil matrix compared with the main compound and less reactive in the case of imidacloprid-urea. Recent studies focused on the degradation of imidacloprid under laboratory and field conditions (Horwood, 2007;Anhalt et al, 2008). In these studies, imidacloprid metabolites were not quantified.…”
Section: Desorption Hysteresismentioning
confidence: 99%
See 1 more Smart Citation
“…Cox et al (1997) conducted sorptiondesorption of imidacloprid and its three metabolites and reported that metabolites such as the imidacloprid-guanidine, possibly produced in our experiment, are more strongly sorbed with the soil matrix compared with the main compound and less reactive in the case of imidacloprid-urea. Recent studies focused on the degradation of imidacloprid under laboratory and field conditions (Horwood, 2007;Anhalt et al, 2008). In these studies, imidacloprid metabolites were not quantified.…”
Section: Desorption Hysteresismentioning
confidence: 99%
“…Imidacloprid is a commonly used insecticide as a soil and foliar treatment for a wide range of crops (Grey et al, 2006;Kreutzweiser et al, 2008). It is effective for sucking insects, soil insects, termites, and several species of biting insects (Horwood, 2007).…”
mentioning
confidence: 99%
“…Such behavior is not surprising with repellent chemicals such as bifenthrin (Smith and Rust 1990) but is less well documented for so-called nonrepellents such as chlorfenapyr (Rust and Saran 2006), Þpronil (Ibrahim et al 2003), and imidacloprid (Gahlhoff and Koehler 2001). Chemical breakdown is unlikely to have been the cause of differences in effectiveness among soil treatments, because bifenthrin and chlorfenapyr, the two least active soil treatments, were shown by Horwood (2007) to have the greatest Þeld longevity of the liquid termiticides tested.…”
Section: Resultsmentioning
confidence: 77%
“…Horwood [29] found that after 15 months, chlorpyrifos and fipronil concentrations at lower depths were little changed from the time of treatment, but there was a major reduction in imidacloprid concentration at all depths. Cai and Henderson [30] their results show that the presence of C. formosanus can suppress the growth of Bti and Btt and the suppression effect enhanced with increased of group size.…”
Section: /7mentioning
confidence: 99%